Model-based patterns in prostate cancer mortality worldwide - Fontes, F (Nature Publishing Group, 2013)
BACKGROUND: Prostate cancer mortality has been decreasing in several high income countries and previous studies analysed the trends mostly according to geographical criteria. We aimed to identify patterns in the time trends of prostate cancer mortality across countries using a model-based approach. METHODS: Model-based clustering was used to identify patterns of variation in prostate cancer mortality (1980–2010) across 37 European, five non-European high-income countries and four leading emerging economies. We characterised the patterns observed regarding the geographical distribution and gross national income of the countries, as well as the trends observed in mortality/incidence ratios. RESULTS: We identified three clusters of countries with similar variation in prostate cancer mortality: pattern 1 (‘no mortality decline'), characterised by a continued increase throughout the whole period; patterns 2 (‘later mortality decline') and 3 (‘earlier mortality decline') depict mortality declines, starting in the late and early 1990s, respectively. These clusters are also homogeneous regarding the variation in the prostate cancer mortality/incidence ratios, while are heterogeneous with reference to the geographical region of the countries and distribution of the gross national income. CONCLUSION: We provide a general model for the description and interpretation of the trends in prostate cancer mortality worldwide, based on three main patterns.